Joint statement of the german respiratory society and german society of thoracic surgery in cooperation with the german radiological society: structural prerequisites of centres for interventional treatment of emphysema - Gesierich, Wolfgang; Darwiche, Kaid; Döllinger, Felix; Eberhardt, Ralf; Eisenmann, Stephan; Grah, Christian; Heußel, Claus Peter; Huebner, Ralf-Harto; Ley-Zaporozhan, Julia; Stanzel, Franz; Welter, Stefan; Hoffmann, Hans (Respiration, 2021)
Bronchoscopic lung volume reduction; Emphysema; Interventional treatment; Lung volume reduction surgery; Structural prerequsites